(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background Enterobius vermicularis causes pinworm infection which is extremely common in human beings; especially among children. A cross-sectional study (2023-2024) involving 1213 school children with the age of 3-9 years old in four districts of Khyber Pakhtunkhwa Province, which represents a rural population of students, investigated epidemiology and risk factors of E. vermicularis infection. Methods Simple random sampling method was used in selecting the Two kindergartens and Two primary schools in each of the districts. The adhesive cellophane tape technique was used in the perianal swabbing during the process of detecting pinworm infection. Information regarding demographics and hygienic practices and environment at school was determined on the basis of structured questionnaires. All of the possible risk factors entered into simple logistic regression and factors with a P of less than 0.1 were chosen to enter the multivariate examination that was done through logistic regression. Result The cumulative infection rate was 5.19%, with maximum 11.51 percent in Tank District, Karak (3.76 percent), Lakki Marwat (3.31 percent) and D. I. Khan (2.7%). The positive rate at the boy level was more than the girls (6.98% vs. 3.30%, P=0.0031). Within boys, Older age was also found to cause an increase in the infection rate (P = 0.186) with the maximum prevalence occurring among 8-year-olds (6.29%). Other than that, the infection rate of the subjects at the primary school was higher compared to that of the subjects in kindergarten (7.17% vs. 2.39%). Among the girls there were no significant differences in the group. In addition, regular disinfection of classrooms and monthly health and educational programs were revealed in connection with the reduced level of infection. Conclusion The research paper establishes the high infections of E. vermicularis by the schoolchildren in KPK Province as a result of rural inhabitants and some of the major risk factors. Hygiene education and sanitation would be significant interventions that should be highly emphasized especially among the male students since this practice would facilitate control of E. vermicularis infection.